2022
DOI: 10.1371/journal.pone.0267287
|View full text |Cite
|
Sign up to set email alerts
|

Flow-mediated slowing shows poor repeatability compared with flow-mediated dilation in non-invasive assessment of brachial artery endothelial function

Abstract: Pulse wave velocity (PWV) deceleration to reactive hyperemia–flow-mediated slowing (FMS)–has been suggested as an alternative method to flow-mediated dilation (FMD) to evaluate brachial artery endothelial function. FMS is suggested to address major caveats of the FMD procedure including its suboptimal repeatability and high-operator dependency. However, the repeatability of FMS has not been thoroughly examined, especially given the plethora of methods claiming to measure PWV. We assessed and compared the intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
1
3
2
Order By: Relevance
“…Both raters demonstrated good to excellent intra-and inter-day repeatability in the offline analyses of local estimates of FMS and FMD [7,32]. These findings are contradictory to those from regional FMS (CV > 100%) published earlier by this research group [15], but aligned with the FMS repeatability reported by Ellins et al [11]. Together, this suggests that the heterogeneity in viscous-elastic properties of the arteries is likely the main confounder in regional FMS including both elastic and muscular arteries.…”
Section: Intra-rater Repeatabilitycontrasting
confidence: 77%
See 3 more Smart Citations
“…Both raters demonstrated good to excellent intra-and inter-day repeatability in the offline analyses of local estimates of FMS and FMD [7,32]. These findings are contradictory to those from regional FMS (CV > 100%) published earlier by this research group [15], but aligned with the FMS repeatability reported by Ellins et al [11]. Together, this suggests that the heterogeneity in viscous-elastic properties of the arteries is likely the main confounder in regional FMS including both elastic and muscular arteries.…”
Section: Intra-rater Repeatabilitycontrasting
confidence: 77%
“…However, this conclusion was drawn from a single-rater study, limiting its clinical applicability where multiple raters would evaluate the same patient. In addition, our previous work contradicts this initial report as FMS (CV: 136%) was found to be less repeatable compared to FMD (CV: 25%) [15]. One possible reason for this discrepancy is the heterogeneity in viscoelasticity properties between the upper limb arterial segments used to estimate PWV.…”
Section: Introductioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Studies on flow-mediated dilatation (FMD) and flow-mediated slowing (FMS) in newborns with FGR are scarce. Although these methods are widely accepted for evaluating vascular well-being in adults and older kids, their application in newborns, particularly in FGR, is still nascent (57).…”
Section: Flow Mediated Dilatation ( Fmd) and Flow-mediated Slowing ( ...mentioning
confidence: 99%